Meningkatkan Pemahaman SBdP: Membuat Potpourri dari Bahan Alam Tema 6 Sub Tema 1 (Lingkungan Sehat Masyarakat Sehat) dengan Metode Penugasan di Kelas VI (enam) UPT SD Negeri 172 Gresik - Kasmugi (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
This classroom action research aims: 1) Describe the activities of teachers in increasing understanding of SBdP: making potpourri from natural ingredients. 2) Describing student activities in learning activities to improve understanding of SBdP: making potpourri from natural ingredients. Theme 6 Sub Theme 1 (Healthy Environment for Healthy Communities) with the assignment method in Grade VI (six) UPT SD Negeri 172 Gresik. 3) Describe learning with the assignment method in improving SBdP understanding: making potpourri from natural ingredients. Theme 6 Sub Theme 1 (Healthy Environment for Healthy Communities) in Grade VI (six) UPT SD Negeri 172 Gresik. This research is a collaborative classroom action research. The design of problem situations, and ways of collaboration with children, are the main focus of the meetings that take place between teachers and researchers. This research was conducted at UPT SD Negeri 172 Gresik at the address Jl. Raya Kepuhklagen, Wringinom - Gresik. The subjects of this study were 22 students of Grade VI (six). The research was conducted in the even semester of the 2018/2019 academic year, for 3 months (January, February, and March 2019). Action research procedures are cyclic, namely: 1) planning, 2) implementation, 3) observation, and 4) reflection, through a series of cycles. Data collection through observation (observing), artifacts and documents (testing) and non-standard tests. Instrument test items with validity test, reliability test, calibration test (level of difficulty) and distinguishing power test. The whole data analysis process is interactive using the Miles and Huberman model with the final mix method analysis. The results of the study concluded: 1) Teacher activity increased in Pre-Action, which resulted in 62.86 percent and increased in Cycle I by 72.86 percent and increased in Cycle II by 86.43 percent; 2) Student activity increased in Pre-Action to get 42.86 percent and increased in Cycle I by 65 percent and increased in Cycle II by 86.43 percent .; 3) The average value of the test (Classical Absorption) has increased in Pre-Action, obtaining 68.4 percent results and an increase in Cycle I by 72.95 percent and an increase in Cycle II by 80.22 percent. Classical learning completeness has increased in Pre-action obtained 36.36 percent results and increased in Cycle I by 54.55 percent and increased in Cycle II by 86.36 percent.